DOCTOR’S RHETORICAL STYLE IN CONVEYING CRITICAL ILLNESS DIAGNOSE TO THE PATIENT’S FAMILY - Tri Agus Yuarsa; Ahmad Sihabudin; Ridzki Rinanto Sigit; Dewi Widowat2 (International Journal of Social Science, 2024)
Rhetoric is an art of speaking used by someone to convey knowledge, information, and issues to public with the intention of building trust, so that the initial goal will be achieved. Rhetoric is a field that studies and delves into how to speak in a charming manner, so that the audience can understand and be captivated by the conversation. In other words, rhetoric is the science of the art of speaking. RESEARCH PURPOSES The aim is to determine the rhetorical style of doctors in conveying diagnoses of critical illnesses to patient families. and how physicians can modify their rhetorical styles to achieve better understanding and support of patients and their families. RESEARCH METHODS Mixed methods is an approach where researchers use both qualitative data (such as interviews, observations) and quantitative data (such as surveys, experiments) to answer research questions. By using mixed methods, researcher can gain a more complete and in-depth understanding of the issue or research problem, blending statistical accuracy with richer social or behavioral context. By combining quantitative data (which is objective and measurable) with qualitative data (which is objective and measurable), researchers can obtain a more comprehensive picture of the phenomenon being studied. RESULTS A doctor's rhetorical style, namely the way how the doctors communicate with patients, has a significant influence on the effectiveness of medical services. Good communication between doctors and patients is not just about conveying medical information, but also involves how the information is delivered so that the patient feels heard, appreciated and supported. Care for critical illnesses requires tight coordination between various specialists and medical disciplines to provide optimal and integrated care for patients. The goal is not only to prolong life but also to improve the quality of life of patients and their families. CONCLUSION The relationship between rhetorical style, Newcomb ABX Theory, and critical illness is closely related to effective communication in a medical context, especially in treating patients with serious health conditions. Each of these elements plays an important role in ensuring that medical information is delivered in a way that supports patient understanding, shared decisions, and emotional management